ANALISIS MANAJEMEN PIUTANG PENDAPATAN JASA LAYANAN PADA RSUD Dr. SOETOMO - Rendy Fadhlan Putra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research tries to analyze the management of service income receivable at RSUD Dr. Soetomo. The discussion includes the policy of services income receivable management, internal control of accounts receivable and management of the uncollectible account receivable. The data used in this study is the result of interviews at admission division and accounting division of RSUD Dr. Soetomo as parts involved in service income receivable management. The primary data is obtained from RSUD Dr. Soetomo in the form of documentation.The results of this research indicate that service income receivable management and internal controls have been implemented well. However, there is a little problem in receivables collection from individual patients. Furthermore, different rates in determining claims to BPJS cause correction of accounts and delays in payments from BPJS to the hospital. Keywords: Services Income Receivable Management, Internal Control, Uncollectible Account Receivable, Hospital